2005
DOI: 10.1007/s10549-005-7697-7
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Beta (ESR2) Polymorphisms in Familial and Sporadic Breast Cancer

Abstract: Estrogen is involved in both normal mammary development and in breast carcinogenesis. A family history of disease and exposure to estrogen are major risk factors for developing breast cancer. Estrogen exerts its biological effects through binding to the estrogen receptors, estrogen receptor alpha (ESR1) and the more recently discovered estrogen receptor beta (ESR2). Genetic variation in genes involved in estrogen biosynthesis, metabolism and signal transduction have been suggested to play a role in breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 35 publications
0
41
1
Order By: Relevance
“…Polymorphisms or haplotypes in ESR2 have been associated with an increased risk for a number of estrogen-related disorders, including osteoporosis [47,48,49,50,51], breast cancer, ovarian cancer [52,53,54,55,56,57,58,59,60] and polycystic ovarian disease [61]. ER-β is found in high concentrations in the hippocampus [51], and its activation has been linked to synaptic plasticity and hippocampal-dependent cognition [13,62].…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms or haplotypes in ESR2 have been associated with an increased risk for a number of estrogen-related disorders, including osteoporosis [47,48,49,50,51], breast cancer, ovarian cancer [52,53,54,55,56,57,58,59,60] and polycystic ovarian disease [61]. ER-β is found in high concentrations in the hippocampus [51], and its activation has been linked to synaptic plasticity and hippocampal-dependent cognition [13,62].…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al identified 2 ESR2 SNPs associated with increased breast cancer risk in postmenopausal but not in premenopausal women (12). A recent study of 3 ESR2 SNPs found no association of the individual SNPs, but 1 haplotype of these SNPs was identified that was associated with an increased risk of sporadic breast cancer (13). Further analysis of the functional consequences of SNPs for ESR1 and ESR2 and association of SNPs in particular subject study groups, as well as identification of novel SNPs, may shed further light on the hereditary contributions to the development of breast cancer.…”
Section: Ers and Cancer Breast Cancer Estrogen Is Implicated In The mentioning
confidence: 98%
“…Estrogen plays a central role in the normal development of the mammary gland but is also involved in breast cancer progression (3) .…”
Section: Introductionmentioning
confidence: 99%